Analysis of the Influencing Factors of Inventory Management of listed Companies in Shandong Province - Liu, Zichun (International Journal of Global Economics and Management, 2024)
This paper studies the inventory management of 25 listed companies in Shandong Province, and uses the current ratio, return on equity, inventory turnover and other indicators to analyze the inventory management of different industrial companies and the main influencing factors. Throug h descriptive analysis, correlation analysis, factor analysis and other methods, a linear regression model is constructed to determine the relationship between inventory management and its influencing factors, and suggestions and countermeasures are put forward to provide reference for the improvement of inventory management of listed companies in Shandong P rovince and the balanced long-term development of the industry.